Numerical studies of radiofrequency of the electromagnetic radiation power absorption in paediatrics undergoing brain magnetic resonance imaging. Issue 3 (July 2017) - Subaar, C.; Amoako, J.K.; Owusu, A.; Fletcher, J.J.; Suurbaar, J.
Abstract: Magnetic resonance imaging current operating frequencies are above 100 kHz which is converted to heat through resistive tissue losses during imaging. The imaging is coupled with a concurring increase in temperature in patients. Magnetic resonance imaging of the brain has seen a rising clinical request during diagnosis and therefore become imperative that its safety issues be assessed. This study modelled Pennes' classical bio-heat equation using Finite Difference Method (FDM) approach and with the help of MATLAB programming language, predicted three dimensional steady state temperature distributions in patients during magnetic resonance imaging. Sixty-four paediatric patients' referred for (head) brain magnetic resonance imaging scan at 37 Military Hospital and the Diagnostic Center Limited, Ghana, pre-scan and post-scan temperatures were measured at the right tympanic. The numerically steady state temperature distribution during magnetic resonance imaging shows that there is excessive temperature elevation at the skin surface of the patients. The resulting skin heating during magnetic resonance imaging can reach dangerous level which suggests that the ohmic heating of tissue is greatest at the surface and minimal at the center of the patient's brain. Though the experimental results show that patients brain temperature increase after imaging, all measured temperatures were within acceptable safe levels.